Relationship between Insulin Secretion and Arterial Stiffness in Essential Hypertension. (24th December 2021) - Sun, Yancui; Zhu, Yanqiu; Zhang, Lu; Lu, Yan; Liu, Yan; Zhang, Ying; Song, Wei; Jiang, Yinong; Cheng, Yunpeng
Abstract : The study aims to explore the relationship between plasma insulin secretion and arterial stiffness in nondiabetic essential hypertensive patients. A total of 730 nondiabetic essential hypertensive patients registered between January 2016 and October 2020 were enrolled. A two-hour oral glucose tolerance test (OGTT) was performed to detect the levels of C-peptide and blood glucose at 0 hours and 2 hours, as well as the difference between C-peptide (Δ C-peptide) and blood glucose (Δ blood glucose) over the same period. Patients were divided into two groups: the normal glucose tolerance (NGT) group ( n  = 322) and the impaired glucose tolerance (IGT) group ( n  = 408). A multiple linear regression analysis was used to evaluate the association between brachial-ankle pulse wave velocity (baPWV) and the other factors. 0 h C-peptide, 2 h C-peptide, and Δ C-peptide were found to be higher in the IGT group. baPWV was positively linear correlated with 2 h C-peptide ( r  = 0.086, p = 0.020 ) and Δ C-peptide ( r  = 0.115, p = 0.002 ). baPWV remained independently associated with 0 h C-peptide, 2 h C-peptide, and Δ C-peptide, after adjusting by age, gender, smoking, body mass index (BMI), high-density lipoprotein (HDL), cholesterol, systolic blood pressure (SBP), and triglycerides (TG). Our data shows that higher endogenous insulin secretion might play an important role in the progression of arterial stiffness in nondiabetic essential hypertensive patients.